AS PRÁTICAS DE SUSTENTABILIDADE NA CONSTRUÇÃO CIVIL: UM ESTUDO COM OS CONSTRUTORES DE UNIDADES HABITACIONAIS HORIZONTAIS - SILVA, Artur Souza Gondim (2022)
This research aimed to analyze the sustainability practices inserted in the context of the construction of popular horizontal housing units in the city of São Luís. It is a descriptive and exploratory research with the application of a questionnaire. The study sample consisted of 26 builders. The results of the study highlight that the use of technologies aimed at sustainability in civil construction of popular housing units tends to generate great benefits not only for the environment, but also can offer significant comfort to its residents, and that this study demonstrates the maximizing the preservation of the environment in which they are located. It is concluded that the results of this research can help construction companies to achieve competitive advantages by encouraging a strong market orientation through the development of technologies, techniques and practices based on sustainability. In this way, the present study presents itself to contribute to the market for the construction of housing units in the sense of, through the observation of the researched technologies, allowing the builders to evolve their products offered to the market to be able to count on a superior performance to the others also in the scope of the sustainability.